Perancangan, Fabrikasi, dan Karakterisasi Transistor Bipolar: Perancangan, Fabrikasi, dan Karakterisasi Transistor Bipolar - Subandi, Ayub; Idris, Irman (Komputika : Jurnal Sistem Komputer, 2025)
Bipolar transistors still play an important and irreplaceable role in the application of electronic systems, even though almost all logic circuits, including microprocessors and memory, consist of MOS (Metal Oxide Semiconductor) transistors. They are widely used today due to their advantage higher switching speed compared to MOS technology and their ability to conduct high currents. In this research, the design, fabrication, and characterization of bipolar transistor were carried out. The design was done using L-Edit software and the converted to glass using a photoreduction camera. The base material for the transistors was n-type epitaxial wafer with a layer depth of 3 μm. The fabrication process involved wafer cleaning, oxidation, diffusion, photolithography, etching, metallization, and metal strengthening. Due to the use of a thin epitaxial wafer, thermal diffusion followed by a drive-in process was avoided to prevent penetration through the epitaxial layer, resulting in a low current gain (β) of only 1.5 times. On the other hand, using a thicker epitaxial layer would create difficulties during the isolation process. The success of each fabrication step was determined by measurement on test patterns, including resistor resistance measurement, diode characterization, and determination of diffusion depth using dummy samples. The measurement results showed an emitter junction depth of 0.3 μm, and a base layer width of 1.1 μm. These results indicate that the transistor was successfully fabrication, although with a low current gain. Keywords – MOS; Epitaxial wafer; Diffusion; Current amplifier; Dummy.